Responsible leadership actions and achievement of societal purpose: Perspectives from the Kenyan health NGO sector - Angela C. Ng’etich; Eric E. Mang’unyi (Health Economics and Management Review)
The primary goal of this study was to provide empirical evidence to improve understanding of how responsible leadership actions drive the societal purpose of health non-governmental organisations (NGOs). What impact have such efforts had on organizational performance in terms of achieving societal goals? Although researchers continue to investigate the domain of responsible leadership, none have focused on the health NGO sector, particularly in developing countries, and with a focus on providing evidence-backed adaptation practices for the future. A cross-sectional mixed study approach was applied, with positivist and constructivist phenomenological viewpoints being incorporated. The study respondents were sustainable health system experts working in health NGOs on a national and international scale as well as the health ministry. The perspectives of 33 randomly selected respondents were gathered using a cross-sectional questionnaire survey and 10 purposively selected key informants using open-ended interview questions were empirically and thematically analysed respectively. The findings indicate that responsible leadership embedded on organisational purpose benefits the organisation and adds value to society. Responsible leaders in the studied organisations built trust, used open communication, mindful actions and collective consciousness to positively and effectively engage with their employees. The prospection and future-orientation of responsible leaderships of health NGOs could stimulate adaptive responses in postmodern society, allowing them to deepen sustainable value for society. Leadership actions are an essential component of these NGO adaptation to change. That must be taken into account by managers for smooth adjustments to the changing context, allowing these NGOs to remain relevant and authentic to their organisations’ societal purpose. Despite the fact that researchers are continuing to investigate the domain of responsible leadership, no one has focused on the health NGO sector in developing countries like Kenya. The empirical evidence in this article shows that responsible purpose-driven leadership, combined with responsible actions, has an impact on organisations’ adaptation to contextual changes.